Osmotic demyelination as locked in syndrome - Hari, Parvathi S.; Hari, Gayathri S.; Prabhakar, Praveen (International Journal of Research in Medical Sciences, 2024)
Osmotic demyelination syndrome (ODS), also known as central pontine myelinolysis, is a disorder that affects the pons and extrapontine regions. This condition clinically presents with a multitude of neurological manifestations. The pathogenesis of ODS is not yet clearly understood. Most common cause of ODS is iatrogenic rapid correction of hyponatremia with a bolus of hypertonic saline. Very rarely it can be directly caused by alcohol intoxication and disrupted neuronal metabolism due to deficiency of essential substrates. A 34-year-old chronic alcoholic male presented with neurological symptoms and signs for 2 days. Clinical examination suggested multifactorial encephalopathy which was attributed to hyponatremia, Wernickes and hepatic encephalopathy substantiated by abnormal lab reports and unremarkable initial magnetic resonance imaging (MRI) findings. Although his sensorium improved over the next 3-4 days following slow correction of hyponatremia, parenteral thiamine and vitamin B12, B6 and B3, he suddenly went into a mute state followed by quadriparesis which aroused the suspicion of locked-in syndrome. Since his quadriparesis was accompanied by mutism and emotional incontinence, a lesion above cervical spine was suspected. So a repeat MRI brain was taken which showed development of demyelination of ventral pons, bilateral lentiform and caudate nucleus, posterior limb of internal capsule and both thalami which were conjunct with pontine and extrapontine ODS. Outcome of an established ODS cannot be predicted. Early diagnosis of ODS is a serious challenge as demyelination can be missed in initial MRI scan. So, a repeat MRI based on meticulous clinical assessment is crucial for early diagnosis and timely intervention.